Black religion in the madhouse: race and psychiatry in slavery's wake - Weisenfeld, Judith (New York University Press, 2025)
"Black Religion in the Madhouse traces the encounter between African Americans and American psychiatry in the decades after the end of slavery and into the twentieth century, showing how white psychiatrists pathologized African American religion and exploring the implications of these theories and practices for Black patients"--